2019
DOI: 10.1021/acs.jpcc.9b06848
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Friction Reduction of Two-Phase Flows on Surfaces Using 3D Hierarchical Nanostructures

Abstract: The use of superhydrophobic surfaces is one the most promising methods for reducing the friction and increasing the flow rate in fluid transfer systems. Because in such systems the surface structure plays a key role, in this study, we explore the performance of the hierarchical nanostructures. These nanostructures are inspired by the superhydrophobic surface of the lotus leaf. We consider a flow between two walls with hierarchical nanostructures and simulate the system via the molecular dynamics method. The si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Currently, try to increase the mass transport in nanochannels through changing the slip length has been an important subject of a growing number of studies. By constructing nanostructures on channel surfaces, both the contact area between the fluid and the solid wall as well as the surface wettability can be changed, accompanied by the adjusted slip length 190,191 . It was reported that a nanochannel with densely fluorous surface exhibits ultrafast water permeation flux, which is two orders of magnitude greater than those of aquaporins and carbon nanotubes 192 …”
Section: Properties and Characteristicsmentioning
confidence: 99%
“…Currently, try to increase the mass transport in nanochannels through changing the slip length has been an important subject of a growing number of studies. By constructing nanostructures on channel surfaces, both the contact area between the fluid and the solid wall as well as the surface wettability can be changed, accompanied by the adjusted slip length 190,191 . It was reported that a nanochannel with densely fluorous surface exhibits ultrafast water permeation flux, which is two orders of magnitude greater than those of aquaporins and carbon nanotubes 192 …”
Section: Properties and Characteristicsmentioning
confidence: 99%
“…There are numerous methods that can be used to simulate the droplet states on superhydrophobic surface. From the microscale state, molecular dynamics (MD) study the flow behavior of statistical fluid from the perspective of molecular atoms to explore the wetting state transition of droplets at molecular scale [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The simulation dynamics are sometimes given by the Monte Carlo method.…”
Section: Fundamental Wetting Theorymentioning
confidence: 99%
“…The existence of optimal nanostructure layout at maximum flow rate is also worth further exploration. Saleki et al [71] used lotus leaf nanostructures as the research model to explore the existence of the layout of nanostructure corresponding to the maximum flow rate by simulating the flow between hierarchical nanostructures. Experiments confirm that the maximum flow rate does exist in the designed nanochannel.…”
Section: Dimension and Arrangement Of Particlesmentioning
confidence: 99%